2011
DOI: 10.1111/j.1601-5037.2011.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and evaluation of computer‐assisted education in an undergraduate dental hygiene course

Abstract: The present results suggest that the students became conscious of their lack of knowledge through SLMs. These findings indicate that SLMs for practicing basic clinical procedures is beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Distance education with which students are satisfied is also gradually gaining prevalence . In fact, some schools of dental hygiene have commenced using computer technology in education, which is also recognized as being beneficial for students . Going and studying abroad is not the only way to teach international programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Distance education with which students are satisfied is also gradually gaining prevalence . In fact, some schools of dental hygiene have commenced using computer technology in education, which is also recognized as being beneficial for students . Going and studying abroad is not the only way to teach international programmes.…”
Section: Discussionmentioning
confidence: 99%
“…This tool allows educators who are not computer specialists to create simulation-based medical and dental learning modules. 20,21 The scenario utilised for the CAL modules was based on a clinical case that was treated in the dental hospital of the university in Tokyo. Both the CAL module and the VL module dealt with the same case study.…”
Section: Learning Materialsmentioning
confidence: 99%
“…7 Most e-learning materials can only be accessed on a personal computer (PC). [8][9][10] However, some studies have shown that young people prefer to use their smartphones to access the Internet, 11 which means that they use smartphones as information devices more than PCs. In fact, 99.4% of Japanese adults in their 20s possess a smartphone, 12 and this rate is also increasing in other many countries.…”
Section: Information and Communication Technology And Electronic Learn-mentioning
confidence: 99%
“…Information and communication technology and electronic learning systems (e‐learning) have been gradually introduced in dental education, and positive effects have been identified 7 . Most e‐learning materials can only be accessed on a personal computer (PC) 8‐10 . However, some studies have shown that young people prefer to use their smartphones to access the Internet, 11 which means that they use smartphones as information devices more than PCs.…”
Section: Introductionmentioning
confidence: 99%